Isomorphism Pressure to Micro-Business Decision on Digital Payment Acceptance in SME Indonesia - Riani Lisyiana; Sung Suk Kim (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The Indonesian government and financial institutions have promoted the adoption of digital payments among small businesses to improve efficiency and economic inclusion. This study aims to examine the factors influencing micro sellers’ intention to adopt non-cash payment technology. A quantitative approach was employed, with an estimated population of 876 sellers in Pasar Wisma Asri, North Bekasi. Data were collected using questionnaires and analyzed using PLS-SEM through SmartPLS. The results indicate that coercive pressure from government regulations and normative pressure from industry standards significantly and positively affect sellers’ intention to use digital payment technology. Mimetic pressure contributes to the formation of social norms but does not directly motivate the intention to adopt the technology. Normative isomorphism shows a significant direct effect on intention, suggesting that professional pressure and normative standards strengthen adoption intentions even without increasing subjective norms. Subjective social norms were found to have no significant effect on usage intention in the traditional market context studied. This study expands understanding of non-cash payment adoption through institutional pressures and subjective norms, and provides insights for policymakers, business actors, and stakeholders in designing strategies to accelerate digital payment adoption in the informal sector, thereby supporting financial inclusion and economic welfare.